Analisis Kinerja Keuangan Perusahaan PT Garuda Indonesia Dengan Metode EVA Tahun 2019-2023 - Zaidan Rahadian; Sungkono (CV. ITTC INDONESIA, 2024)
Analyzing financial performance For it get an edge or establish itself as a superior entity, a company must possess a comprehensive understanding its effectiveness, efficiency, and sustainability. In late 2019, Indonesia experienced starting of the COVID-19 pandemic, often known as the coronavirus sickness. The aviation industry was particularly impacted, leading to an economic decline. The objective of the study is to assess the financial performance of PT Garuda Indonesia (Persero) Tbk using the EVA approach to ascertain the company's economic added value during the pre-covid period, the covid period, and the time of endemic changes in covid-19. The EVA method is a quantitative approach used to assess a company's financial performance and aid investors in making investment decisions in the capital market. The analysis utilizes data obtained from the Indonesia Stock Exchange (BEI). The research findings indicate that PT Garuda Indonesia (Persero) Tbk has generated a negative Economic Value Added (EVA), implying that the company is not generating sufficient returns to cover its cost of capital. This suggests that the financial performance of PT Garuda Indonesia (Persero) Tbk was poor both before the pandemic, during the pandemic, and during the transition to the endemic phase of the Covid-19.